An Isolated Nitridyl Radical‐Bridged Rh(N.)Rh Complex1. (19th May 2014) - Gloaguen, Yann; Rebreyend, Christophe; Lutz, Martin; Kumar, Pravin; Huber, Martina; van der Vlugt, Jarl Ivar; Schneider, Sven; de Bruin, Bas
Abstract Photochemical activation of [(PNNH)Rh(N3)] (PNNH=6‐di‐(tert‐butyl)phosphinomethyl‐2, 2′‐bipyridine) complex 2 produced the paramagnetic (S=1/2), [(PNN)RhN.‐Rh(PNN)] complex 3 (PNN−=methylene‐deprotonated PNNH), which could be crystallographically characterized. Spectroscopic investigation of 3 indicates a predominant nitridyl radical (.N2−) character, which was confirmed computationally. Complex 3 reacts selectively with CO, producing two equivalents of [(PNN)RhI(CO)] complex 4, presumably by nitridyl radical N, N‐coupling.